Mental Health and Work Experiences of Interpreters in the Mental Health Care of Refugees: A Systematic Review - Geiling, Angelika; Knaevelsrud, Christine; Böttche, Maria; Stammel, Nadine (Frontiers in Psychiatry, 2021)
Background: Interpreters often play a crucial role in the health care of refugees. Although interpreters working with refugees are regularly confronted with emotionally stressful content, little is known about their work-related stress and psychological well-being. Primarily qualitative studies indicate increased emotional stress in interpreters, and difficulties in handling the traumatic content from their clients. Additionally, the working conditions of interpreters appear to be demanding, due to low payment and a lack of supervision or adequate preparation. Objective: The presented systematic review aimed to identify and summarise quantitative and qualitative research on the mental health of interpreters in the mental health care of refugees. Method: A systematic search was performed in five databases, and specific interpreting journals were searched. After removal of duplicates, 6920 hits remained. Eligible studies included quantitative, qualitative and mixed-methods studies as well as case studies and grey literature. The studies aimed to examine mental health aspects or work experiences of spoken language interpreters in mental health care settings for adult refugees. Results: Altogether, 25 studies were identified, including six quantitative and 19 qualitative studies. Studies were analysed and presented narratively. In the analysis of the qualitative studies, three themes emerged: “Emotions, behaviour, and coping strategies”, “Working in a triad”, and “Working environment”. In the quantitative studies, interpreters showed heightened levels of emotional stress and anxiety, and secondary traumatic stress reactions. In several qualitative studies, interpreters described a devaluing health care system and stressful working conditions with a lack of support structures. Conclusion: Overall, the results indicate a high level of stress among interpreters working with refugees. Quantitative data are sparse, and studies employ heterogeneous assessments in diverse study settings. Therefore, future quantitative research is necessary to consistently investigate interpreters’ mental health in different mental health care settings.